2013
DOI: 10.1134/s0021364013180057
|View full text |Cite
|
Sign up to set email alerts
|

Exchange relaxation as a mechanism of the ultrafast reorientation of spins in a two-sublattice ferrimagnet

Abstract: In the exchange approximation, an exact solution is obtained for the sublattice magnetizations evolution in a two-sublattice ferrimagnet. Nonlinear regimes of spin dynamics are found that include both the longitudinal and precessional evolution of the sublattice magnetizations, with the account taken of the exchange relaxation. In particular, those regimes describe the spin switching observed in the GdFeCo alloy under the influence of a femtosecond laser pulse.PACS numbers: 75.10. Hk, Magnetic materials have v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 13 publications
3
49
0
1
Order By: Relevance
“…A nonlocal damping mechanism due to spatial dispersion of the exchange field was proposed by Bar'yakhtar on the basis of phenomenological considerations such as symmetry arguments and Onsager's relations [10]. This leads to a modified expression for the damping term in the Landau-Lifshitz-Bar'yakhtar equation which contains the derivative of the exchange field ∇ 2 B xc [10,20]. The existence of such nonlocal damping term can be related to the continuity equation connecting the spin density and spin current; it is important for obtaining the correct asymptotic behavior of spin wave damping at large wavevectors k [20] known for magnetic dielectrics, see [59].…”
Section: Exchange Field and Nonlocal Contributionsmentioning
confidence: 99%
See 2 more Smart Citations
“…A nonlocal damping mechanism due to spatial dispersion of the exchange field was proposed by Bar'yakhtar on the basis of phenomenological considerations such as symmetry arguments and Onsager's relations [10]. This leads to a modified expression for the damping term in the Landau-Lifshitz-Bar'yakhtar equation which contains the derivative of the exchange field ∇ 2 B xc [10,20]. The existence of such nonlocal damping term can be related to the continuity equation connecting the spin density and spin current; it is important for obtaining the correct asymptotic behavior of spin wave damping at large wavevectors k [20] known for magnetic dielectrics, see [59].…”
Section: Exchange Field and Nonlocal Contributionsmentioning
confidence: 99%
“…This leads to a modified expression for the damping term in the Landau-Lifshitz-Bar'yakhtar equation which contains the derivative of the exchange field ∇ 2 B xc [10,20]. The existence of such nonlocal damping term can be related to the continuity equation connecting the spin density and spin current; it is important for obtaining the correct asymptotic behavior of spin wave damping at large wavevectors k [20] known for magnetic dielectrics, see [59]. Such nonlocal damping is important, too, for describing spin current flow in magnetic metallic heterostructures [78].…”
Section: Exchange Field and Nonlocal Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] it was suggested that translational motion of domain structure (DS) is caused by various inhomogeneities that lead to di erent conditions on the neighboring DW. Analytical theory of drift was proposed in [3].…”
Section: Introductionmentioning
confidence: 99%
“…The LLBar equations are well suited for description of non-uniform states, like magnetic solitons [14,15] and Bloch points [16], and give the explanation of the reversal effects [17,18]. These equations provide an explanation of recent experiments on magnetization recovery in laserpumped Ni-Ru-Fe heterostructures [19], where the importance of the nonlocal character of the magnetization recovery is established [13].…”
Section: Introductionmentioning
confidence: 99%